2021
DOI: 10.3390/v13030483
|View full text |Cite
|
Sign up to set email alerts
|

Human Protoparvovirus DNA and IgG in Children and Adults with and without Respiratory or Gastrointestinal Infections

Abstract: Three human protoparvoviruses, bufavirus (BuV), tusavirus (TuV) and cutavirus (CuV), have recently been discovered in diarrheal stool. BuV has been associated with diarrhea and CuV with cutaneous T-cell lymphoma, but there are hardly any data for TuV or CuV in stool or respiratory samples. Hence, using qPCR and IgG enzyme immunoassays, we analyzed 1072 stool, 316 respiratory and 445 serum or plasma samples from 1098 patients with and without gastroenteritis (GE) or respiratory-tract infections (RTI) from Finla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…CuV was initially discovered in diarrheic stool samples of children, with a low prevalence of 1.4% 1 . We have further observed a CuV‐DNA prevalence of 2.5% (7/284) in stools of adults of the same age range as Group 1, all seven had gastroenteritis 12 . In a recent Chinese study, CuV DNA in stools associated with rheumatoid diseases, however, at a prevalence ( < 6%) similar to what we found for CuV IgG in adults 9,29 .…”
Section: Discussionmentioning
confidence: 50%
“…CuV was initially discovered in diarrheic stool samples of children, with a low prevalence of 1.4% 1 . We have further observed a CuV‐DNA prevalence of 2.5% (7/284) in stools of adults of the same age range as Group 1, all seven had gastroenteritis 12 . In a recent Chinese study, CuV DNA in stools associated with rheumatoid diseases, however, at a prevalence ( < 6%) similar to what we found for CuV IgG in adults 9,29 .…”
Section: Discussionmentioning
confidence: 50%
“…In Thailand, 15 adults without diarrhea were all BuV-negative, whereas 3/81 adult patients with diarrhea were BuV-positive [ 10 ]. BuV DNA was detected in 1/227 children without diarrhea in Bangladesh [ 12 ], and in a cohort of 164 children from Malawi where the unique BuV DNA-positive sample belonged to the group without diarrhea [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
“…BuV DNA has been detected in stool samples (prevalence ranging from 0 to 4%), mostly from patients presenting with diarrhea, in many countries. Other populations have been rarely studied and a limited number of patients has been tested: BuV was not found in blood or cerebrospinal fluids (n = 126) in Turkey; Buv DNA was detected in 1/995 in nasal swabs in Finland and 0/44 nasopharyngeal aspirate from Latvia; studies conducted in Finland, Turkey and Thailand detected BuV DNA in diarrheic samples but not in non-diarrheic samples, whereas studies in Bangladesh and Malawi reported BuV DNA in both diarrheic and non-diarrheic samples [6][7][8][9][10][11][12]. The causative role of BuV in gastroenteritis remains unclear, and its association with other clinical presentations remains largely to be explored [5,6,8].…”
Section: Introductionmentioning
confidence: 99%
“…Wieland et al [ 7 ] found CuV DNA more frequently in the skin swabs of human immunodeficiency virus-positive men (17.1%) than in those of healthy controls (3.8%) in Germany. Mohanraj et al [ 27 ] analyzed fecal specimens in cohorts of patients with gastroenteritis in Finland. They showed that the CuV DNA prevalence among individuals older than 60 years (5.1%) was significantly higher than that among individuals younger than below 60 (0.2%).…”
Section: Discussionmentioning
confidence: 99%